2013
DOI: 10.1097/mbp.0b013e32835d101b
|View full text |Cite
|
Sign up to set email alerts
|

Aging attenuates the interarm diastolic blood pressure difference induced by one-arm exercise

Abstract: Aging attenuates the levels and duration of the dIAD induced by one-arm exercise in healthy adults.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…Our previous studies showed that 3-min one-arm exercise induced marked diastolic BP (DBP) decline only in the exercised arm, followed by increase in the inter-arm DBP difference [10]. Furthermore, the inter-arm DBP difference induced by one-arm exercise was age-dependent [11]. However, this action did not induce inter-arm systolic BP difference because the SBP of both arms changed simultaneously during the observation period.…”
Section: Introductionmentioning
confidence: 99%
“…Our previous studies showed that 3-min one-arm exercise induced marked diastolic BP (DBP) decline only in the exercised arm, followed by increase in the inter-arm DBP difference [10]. Furthermore, the inter-arm DBP difference induced by one-arm exercise was age-dependent [11]. However, this action did not induce inter-arm systolic BP difference because the SBP of both arms changed simultaneously during the observation period.…”
Section: Introductionmentioning
confidence: 99%
“…Limitations to this study were that we only used a young, healthy population, therefore, we cannot make any inferences as to the reliability of this measurement in clinical or elderly populations. However, age may attenuate inter-arm differences in the cardiovascular response to unilateral exercise [17]. It should be highlighted that only one cuff (5 cm wide, nylon) was used in the current study.…”
Section: Discussionmentioning
confidence: 99%
“…The specific contents are as follows: before the measurement, the patients are required to empty the bladder, rest in a quiet and comfortable environment for 10–15 min, and take the decubitus position when the blood pressure is measured, with the sleeves rolled up and arms exposed. Two Omron sphygmomanometers of the same model are used to measure the patients' bilateral upper arm blood pressure once every 1 min, for a total of 3 times, to obtain the 3 blood pressure measurements and the average value [ 18 , 19 ]. After the basic data of interarm blood pressure differences are obtained, a relatively narrow sphygmomanometer cuff is used to fix the patient's right upper arm, and the air is inflated to more than 40 mmHg above the patient's systolic blood pressure, so that the brachial artery blood flow is blocked for about 5 minutes, and then, the patient is quickly deflated.…”
Section: General Information and Detailed Methodsmentioning
confidence: 99%